Detection of nicotin in commercial samples of liquids for electronic cigarettes - T. A. Perezhogina; N. A. Duruncha; I. M. Ostapchenko (Новые технологии)
Sale of liquids for electronic cigarettes requires constant monitoring for this product at the market. The article presents the results of the study on the detection of nicotine in commercial samples of liquids for electronic cigarettes, obtained using the procedure for detecting nicotine in liquids for electronic nicotine delivery systems.